When synergic work between general and vascular surgeons makes the difference. - Santos,Marisa D. (2021)
Abstract Introduction: Chronic Mesenteric Ischemia (CMI) resulting from an impaired blood flow of the splanchnic organs is characterized by an insidious clinical course and is often an underestimated and undertreated disease. The natural history is progressive, caused by atherosclerosis progression in a polymorbidity and aging society. Due to collateralization, diffuse stenotic lesions can remain asymptomatic for a long time and usually manifests when an acute medical or surgical event occurs. In those cases, the clinical suspicion is crucial to reach the diagnosis promptly, allowing to preserve the patients’ quality of life and, above all, the patients’ life. Clinical case 1: A 48-year-old woman with a history of smoking goes to the emergency department for hypogastric abdominal pain, nausea, and vomiting. A study was performed by computed tomography angiography (CTA) that demonstrated occlusion of the superior mesenteric artery (SMA) and significant stenosis of the celiac trunk associated with thickening of small bowel suggestive of ischemia. A thrombectomy of the superior mesenteric artery and retrograde stenting of the artery ostium was performed, followed by extensive enterectomy on 24-hour laparotomy. After hospital discharge, the patient had new abdominal complaints, and stent occlusion was documented in the SMA. She underwent an iliohepatic bypass with good results. Clinical case 2: A 76-year-old man previously submitted to a right axillofemoral and femoropopliteal sequential bypass to treat chronic limb-threatening ischemia (CLTI), went to the emergency department with complaints of abdominal pain, vomiting, and constipation. The diagnosis of a subocclusive intestinal syndrome was made, having performed a computed tomography (CT) scan where it was observed the Ileum adhered to the cecum, which was thickened; the celiac trunk and SMA had subocclusive stenosis. The patient underwent primary celiac trunk stenting with a balloon-expandable stent. After celiac artery revascularization, a right colectomy was performed with two segmental enterectomies. Conclusion: Mesenteric ischemia is a severe condition that is often underdiagnosed due to the lack of awareness of most physicians and nonspecific symptoms. The vascular intervention aims to prevent intestinal necrosis, which can lead to the patient’s death. Timely diagnosis is therefore essential, and revascularization must be performed before or at the same time as intestinal surgery. The close collaboration between the general and vascular surgery teams is essential to the success of these cases.